Circ-ABCC1 enhances radioresistance of breast cancer cells via miR-627-5p/ABCC1 axis: Circ-ABCC1 enhances radioresistance of breast cancer cells - Zhang, Cuipeng; Wang, Jing; Wang, Hongwei; Li, Jing (Cellular and Molecular Biology, 2022)
Adjuvant radiotherapy represents the standard of care for breast cancer (BC) following breast-conserving surgery. Tumor recurrence after radiotherapy, attributed to acquired radioresistance, has been a haunting and intractable problem. Therefore, preventions from tumor recurrence are vital for improving survival. Recent evidence has suggested circular RNAs (circRNAs) play a part in regulating the radioresistance of varied cancers, including BC. This research concentrated on a novel circRNA hsa_circ_0003427 (termed as circ-ABCC1), probing its influence on the radio-resistance of BC cells, together with the latent molecular mechanism. For this aim, CCK-8 and colony formation assays monitored the changes in viability and proliferation of radio-resistant BC cells. Caspase-3 activity was examined to evaluate cell apoptosis. Bioinformatics prediction and mechanistic assays were involved to determine RNA interactions. Results showed that Circ-ABCC1 was found to be significantly up-regulated in radio-resistant BC cells, in comparison with the corresponding parental BC cells. As to molecular mechanism, circ-ABCC1 served as the miR-627-5p decoy, consequently increasing ABCC1 expression. Rescue assays uncovered that the suppressive impact of circ-ABCC1 silence on BC cell radio-resistance was allowed to be antagonized by miR-627-5p inhibition or ABCC1 up-regulation. In conclusion, Circ-ABCC1 aggravates the radioresistance of BC cells by targeting the miR-627-5p/ABCC1 axis.